Is serum angiotensin converting enzyme level a useful non-invasive marker for liver fibrosis in patients with chronic hepatitis C? - Akar,Tarik (2018)
Summary Objective: Chronic hepatitis C (CHC) continues to be a critical problem. The liver fibrosis score is the most valuable tool in determining treatment and prognosis. Liver biopsy is still considered a gold method but, due to unmet needs, new non-invasive markers are required. The aim of this study was to investigate any possible relationship between serum angiotensin-converting enzyme (ACE) levels and the stages of liver fibrosis in patients with CHC. Method: A total 100 CHC and 100 healthy subjects were enrolled in this study. The relationship between serum ACE level and the stages liver fibrosis was investigated using three different formats, as follows: (group [G]-I, classic Ishak’s Score from F1 to F6; G-II, mild [F1-2], moderate [F3-4] and severe [F5-6]; G-III, mild [≤ F2] and advanced [F > 2]). The clinical usability of serum ACE level for both groups was also investigated. Results: Median serum ACE levels were higher in the healthy group than in CHC (42.5 [7-119] vs. 36 [7-91] U/I, p=0.002). There was no statistical difference among the three different fibrosis groups (G-I, G-II, G-III, p=0.797, p=0.986, and p=0.874) and no correlation between serum ACE level and the stages of liver fibrosis (r=0.026, p=0.923). The usability of serum ACE for evaluated patients with CHC and healthy subjects were calculated as 47% and 64%, respectively. Conclusion: Our study indicated that there is no relationship or correlation between serum ACE levels and stages of liver fibrosis in patients with CHC. The assessment of serum ACE level using genetically corrected reference values may provide more accurate results.